The class trip - Suzanne, Jamie; Pascal, Francine (New York : Bantam, 1988)
The Sweet Valley Middle School sixth grade takes a trip to an amusement park and Jessica Wakefield disappears. As Elizabeth searches for her sister, she's caught up in a series of adventures.
Keywords: Twins -- Fiction; Schools -- Fiction; Twins -- Fiction; School stories